99mTc-Labeled Cyclic Peptide Targeting PD-L1 as a Novel Nuclear Imaging Probe - Guillermina Ferro-Flores; Blanca Ocampo-García; Pedro Cruz-Nova; Myrna Luna-Gutiérrez; Gerardo Bravo-Villegas; Erika Azorín-Vega; Nallely Jiménez-Mancilla; Emiliano Michel-Sánchez; Osvaldo García-Pérez; Nancy Lara-Almazán; Clara Santos-Cuevas (MDPI AG, 2023)
Recent cancer therapies have focused on reducing immune suppression in the tumor microenvironment to prevent cancer progression and metastasis. PD-1 is a checkpoint protein that stops the immune response and is expressed on immune T cells. Cancer cells express a PD-1 ligand (PD-L1) to bind to the T-cell surface and activate immunosuppressive pathways. This study aimed to design, synthesize, and evaluate a 99mTc-labeled PD-L1-targeting cyclic peptide inhibitor (99mTc-iPD-L1) as a novel SPECT radiopharmaceutical for PD-L1 expression imaging. AutoDock software (version 1.5) was used to perform molecular docking for affinity calculations. The chemical synthesis was based on the coupling reaction of 6-hydrazinylpyridine-3-carboxylic acid with a 14-amino-acid cyclic peptide. iPD-L1 was prepared for 99mTc labeling. Radio-HPLC was used to verify radiochemical purity. The stability of the radiopeptide in human serum was evaluated by HPLC. iPD-L1 specificity was assessed by SDS-PAGE. [99mTc]Tc-iPD-L1 cellular uptake in PD-L1-positive cancer cells (HCC827 and HCT116) and biodistribution in mice with induced tumors were also performed. One patient with advanced plantar malignant melanoma received [99mTc]Tc-iPD-L1. The iPD-L1 ligand (AutoDock affinity: −6.7 kcal/mol), characterized by UPLC mass, FT-IR, and UV-Vis spectroscopy, was obtained with a chemical purity of 97%. The [99mTc]Tc-iPD-L1 was prepared with a radiochemical purity of >90%. In vitro and in vivo analyses demonstrated [99mTc]Tc-iPD-L1 stability (>90% at 24 h) in human serum, specific recognition for PD-L1, high uptake by the tumor (6.98 ± 0.89% ID/g at 1 h), and rapid hepatobiliary and kidney elimination. [99mTc]Tc-iPD-L1 successfully detected PD-L1-positive lesions in a patient with plantar malignant melanoma. The results obtained in this study warrant further dosimetric and clinical studies to determine the sensitivity and specificity of [99mTc]Tc-iPD-L1/SPECT for PD-L1 expression imaging.